Dwarfs in Giants’ Lands: Some Observations on Translating Minor Literatures into High-Impact Cultures – The Case of Slovene Literature in Italy - Ožbot, Martina (Meta, 2011)
The paper deals with questions related to the translation of literatures written in limited-diffusion languages and belonging to low-impact cultures into languages of high-impact cultures. The analysis is centred on the introduction and presence of Slovene literature in contemporary Italy, although the Italian situation shares a great deal of similarity with other situations of asymmetrical translational transfer. In an attempt to identify the elements playing a role in the successful integration of a peripheral literature in a high-impact target culture, four factors are postulated and discussed: a) target extra-textual setting, b) literary and genre-related properties of source texts and criteria for their selection, c) translator’s competence, d) translation strategies employed. It is suggested that a consistently target-oriented approach is central to a positive reception of a peripheral literature in a high-impact target setting.